2017
DOI: 10.1186/s12981-017-0156-9
|View full text |Cite
|
Sign up to set email alerts
|

Clinical characteristics, predictors of immune reconstitution inflammatory syndrome and long-term prognosis in patients with Kaposi sarcoma

Abstract: ObjectiveTo investigate the predictive factors for the development of Kaposi sarcoma-related immune reconstitution inflammatory syndrome (KS-IRIS) and long-term prognosis in patients starting combined antiretroviral therapy (cART).MethodsWe studied a retrospective-cohort of consecutive antiretroviral-naïve patients with KS initiating cART from January 2005 to December 2011 and followed through June 2013. KS-IRIS was defined as ≥2 of the following: abrupt increase in number of KS lesions, appearance or exacerba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
38
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(43 citation statements)
references
References 54 publications
1
38
1
Order By: Relevance
“…While the values found for oral KS‐IRIS (1.9%) in the present study and in the previous one (1.4%) (Ramírez‐Amador et al., 2009) are low, KS is a well‐recognized manifestation in IRIS‐affected individuals developed in up to 39.3% of them; 77% of the cases involve mucosae (Volkow, Cesarman‐Maus, Garciadiego‐Fossas, Rojas‐Marin, & Cornejo‐Juárez, 2017). In this respect, we found that in 2 of the 3 KS cases, skin KS lesions preceded the development of oral KS.…”
Section: Discussioncontrasting
confidence: 63%
“…While the values found for oral KS‐IRIS (1.9%) in the present study and in the previous one (1.4%) (Ramírez‐Amador et al., 2009) are low, KS is a well‐recognized manifestation in IRIS‐affected individuals developed in up to 39.3% of them; 77% of the cases involve mucosae (Volkow, Cesarman‐Maus, Garciadiego‐Fossas, Rojas‐Marin, & Cornejo‐Juárez, 2017). In this respect, we found that in 2 of the 3 KS cases, skin KS lesions preceded the development of oral KS.…”
Section: Discussioncontrasting
confidence: 63%
“…There is no universally accepted definition for KS‐IRIS . However, four features (see Table ) must be present . Based on these features, our case meets the criteria for pediatric KS‐IRIS.…”
Section: Discussionmentioning
confidence: 81%
“…Pulmonary KS-associated immune reconstitution inflammatory syndrome (IRIS) has been described. Volkow et al demonstrated that the median time from starting ART to pulmonary KS-associated IRIS was around 10 weeks 26. A recent retrospective series suggested that starting ART containing integrase inhibitors (particularly raltegravir) in patients with low CD4 count was independently associated with an increased risk of IRIS, but this remains controversial 27.…”
Section: Discussionmentioning
confidence: 99%